2018
DOI: 10.15405/epsbs.2018.12.128
|View full text |Cite
|
Sign up to set email alerts
|

Do Infrastructure Factors Influence Social And Economic Development Of Russian Regions?

Abstract: This article is devoted to an assessment of the influence of infrastructure on social and economic development of the Russian regions. Various approaches to the treatment of concept of infrastructure are considered, especially chosen are industrial and functional approaches. According to the first of them, the infrastructure is considered as the set of the industries and kinds of activity that are providing activity conditions on an area of the country or the region. According to the second, it is considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…With this view, the paper deals with significant social and economic infrastructure that can help increase the standard of living in regions and boost regional economies. The detailed methodology for this research has been suggested in the collective article (Serkova et al, 2018)…”
Section: Problem Statementmentioning
confidence: 99%
“…With this view, the paper deals with significant social and economic infrastructure that can help increase the standard of living in regions and boost regional economies. The detailed methodology for this research has been suggested in the collective article (Serkova et al, 2018)…”
Section: Problem Statementmentioning
confidence: 99%
“…Appropriate land management through right decisions made by agricultural entrepreneurs to provide service infrastructure in the area, including electricity, water and sewage system, not only increase the value of a given land, but also lower the costs of subsequent investments, thus, driving the increase in attractiveness. Such activities require significant financial outlays, which often represents a hindrance to further infrastructural development of micro-enterprises [27][28][29]. However, communes can benefit from state aid and EU funds designed to ensure equal opportunities and close the significant gap between urban and rural areas [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most important factors influencing social development are -needs of individuals and the society, way of life and human development, reproductive process. The social infrastructure in form of health care, education, sport, culture and art promote a sustainable social and economic development of the region and contribute to improvement of citizens' quality of life (Serkova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%